A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 15 PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Yas, Winta Purwanti; Azhar, Fadly; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research was aimed to find out the ability of the second year students of SMAN 15 Pekanbaru in comprehending narrative texts. The subject of this research was class XI IPS 1 which consisted of 32 students. The data were collected by administering a test to the students in the form of multiple choice test. The findings of the research are as following: finding the main idea (75.00), finding the factual information in complication (65.63), finding the factual information in resolution (70.63), finding the meaning of vocabulary (67.50), finding references (71.88), finding inference (51.25), finding social function (73.13). As a conclusion, the highest score was in finding the main ideas (75.00) which categorized into good level, and the lowest score was in finding inference (51.25) which categorized into mediocre level. The implication of the finding is that the second year students of SMAN 15 Pekanbaru should improve their reading skills in order to reach excellent level.Keywords: Reading Ability, Comprehending Narrative Texts.